Avaliação do conhecimento sobre doenças sexualmente transmissíveis (DSTs) e síndrome da imunodeficiência adquirida (AIDS) entre universitários de Ribeirão Preto/SP - Machado, Alcyone A.; Duarte, Geraldo; Gir, Elucir (Brazilian Journal of Sexually Transmitted Diseases, 1997)
ln order to evaluate the knowledge about STD/AIDS among undergraduate students from different areas, we asked undergraduate students from Ribeirão Preto-SP to answer to a questionary constituted by open and closed questions. The students that agreed in participating were identified without names. The answers were categorized as: correct (C), incorrect (I), incomplete understanding (El) and prejudiced (P). For the data analisis, percentage was used. From 1,200 students, a total of961 (80.80%) participated in the investigation. The number of answers was not equivalent to the different itens of the questionary. The area in whid the students is enrolled did not infl.uence on the answers. The most prevalent results are presented. Concerning HIV transmission, in 2,914 answers we got 65.37% categorized as El. 923 (31.68%) as C. Related to 1,888 answers about preventive measures again It HIV/AJDS, 1,625 (86.07%) werecategorized as C and 207 (10.96%) as El. About the preventive measures